Consumer Attitudes Towards Green Products: Exploration of the Role of Functional Values, Emotional Values, and Subjective Norms - Rahayu, Sri; Khiswari, Zain (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Increasing public awareness and concern for environmental preservation has a positive impact on the development of green marketing. This research aims to analyze the influence of functional value and emotional value on consumer attitudes. This research approach uses quantitative research. The population and sample of this research are consumers who have purchased green tissue products. The sampling technique uses Purposive Sampling. This research data comes from primary data. Data collection techniques through surveys, by distributing questionnaires to target research respondents. Research data was processed using PLS SEM software. The results of this research prove that functional value has succeeded in increasing consumer attitudes towards green products. On the other hand, emotional value cannot improve consumer attitudes. This research also shows that subject norms are proven to be unable to play a moderating role in the influence of functional values and emotional values on consumer attitudes. It is hoped that this research will be useful in helping researchers and marketers understand the influence of values on consumers' attitudes towards green products. Keywords: Consumer attitudes, Functional Value, Emotional Value, Subjective Norms, Green marketing